Performance is Reviewed from Motivation, Competency, Discipline and Organizational Culture of UPT PLDPI Employees of the Surakarta City Education Service - Purno, Siswi; Aryati, Ida; Sarsono (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This research uses a quantitative descriptive approach. In this quantitative descriptive research, the author focuses research on Motivation, Ability and Work Discipline which influence the performance of UPT PLDPI Employees at the Surakarta City Education Service. This research was used to see the influence of motivation, ability and work discipline on the performance of UPT PLDPI employees at the Surakarta City Education Service by collecting data using questionnaires, observation and documentation. Research Location UPT PLDPI Office Surakarta City Education Service Jl, Agung Timur 6A Ngemplak Sutan, Mojosongo Jebres Surakarta. In conducting this research, the time required is 6 months from March – September 2023, starting from observation to producing data results and research conclusions. The population in this study were employees of the UPT PLDPI Surakarta City Education Service, totaling 41 employees. The samples taken in this research were 41 employees of the UPT PLDPI Surakarta City Education Service. Questionnaire collection results using multiple linear regression analysis tools with the help of the SPSS 23 application.Based on the results of the analysis that has been carried out, thenMotivation, Competence, Discipline, Organizational culture influence employee performance at UPT PLDPI Surakarta City Education Service.